Plasma Aβ 42:40 ratio tracks with changes in brain amyloid PET SUVr in the core and open label extension of the phase 2 proof of concept study ban2401‐g000‐201 following treatment with lecanemab in subjects with early Alzheimer's disease. (31st December 2021) - Swanson, Chad J; Kanekiyo, Michio; Kaplow, June; Dhadda, Shobha; Irizarry, Michael C; Koyama, Akihiko; Li, David JianJun; Verbel, David; Gordon, Robert; Heanue‐Travers, Helena; Hodgkinson, Mark; Kramer, Lynn D
Abstract: Background: Lecanemab (BAN2401) is a humanized IgG1 monoclonal antibody that preferentially targets soluble aggregated Aβ species (oligomers, protofibrils) and insoluble fibrils. Lecanemab reduced the amyloid PET standard uptake value ratio (SUVr) and slowed clinical decline in an 18‐month Phase 2 proof of concept study in early Alzheimer's disease (Alz Res Therapy 13; 2021). An Open label extension (OLE) with 10 mg/kg IV biweekly lecanemab dosing was implemented after analysis of the Core study, with an intervening gap period off‐treatment ranging from 9‐54 months (mean 24 months). The present study aimed to evaluate longitudinal plasma Aβ 42:40 ratio (C2N PrecivityAD assay) and the relationship to longitudinal amyloid PET in the Core study, gap period, and OLE. Method: The amyloid PET sub‐study in the Core study assessed baseline, 12 months and 18 months SUVr with florbetapir, and participants in the OLE amyloid PET sub‐study were imaged at baseline, 3 or 6 months, and 12 months. Plasma samples were collected at the same timepoints and analyzed as described previously (West et al, Mol Neurodegen 2021). Mean changes from Core or OLE baseline and Pearson correlation coefficients were calculated at the group and individual levels for amyloid PET SUVr and plasma Aβ 42:40 ratio, accounting for repeated measures. Result: OLE subjects with plasma samples (N=121) were evaluated for this analysis. Lecanemab produced dose dependent reductions in PET SUVr, with corresponding increases in plasma Aβ 42:40 ratio in Core and OLE. In the OLE, reductions in PET SUVr were dependent on OLE baseline SUVr; PET reductions in the OLE were inversely correlated with increases in plasma Aβ 42:40 ratio. Changes in plasma Aβ 42:40 ratio were inversely correlated with changes in PET SUVr at the group and individual levels in the Core (group: r=‐0.939, p=0.0056; individual: r=‐0.49; p<0.0001) and OLE (group: r=‐0.907, p=0.0007; individual: r=‐0.31 p=0.0012) studies. Conclusion: Lecanemab dose‐dependent reduction in brain amyloid PET SUVr correlate with increases in plasma Aβ 42:40 ratio. These data align with the OLE clinical data and suggest that plasma Aβ 42:40 ratio has the potential to track the anti‐amyloid effects of lecanemab in AD patients.